Living in the Making of History! Two Victorian Female Travellers’ Representations of the 1879 Anglo-Zulu War - Ludmila Ommundsen (Cahiers Victoriens et Edouardiens)
At the beginning of the twentieth century a quarter of the Earth’s surface was under British rule. Set in exotic places and recounting terrifying adventures with strange peoples, travel books enjoyed great popularity in the Victorian era and contributed to the culture of the imperial years. In 1877 the Zulu kingdom remained a major obstacle to Lord Carnarvon’s scheme to federate Natal and the Cape Colony with the Boer Republics. Two years later it was invaded and eventually annexed to Natal in 1887. In the late 1870s and early 1880s two courageous women travelled to South Africa: Mrs Louisa Hutchinson, married to an army officer, who wrote In Tents in the Transvaal (1879) and Lady Florence Douglas Dixie—the first female war correspondent—who published In The Land of Misfortune (1882). Admittedly, Hutchinson’s and Dixie’s journeys were an expression of protest and power. If the Zulus were being erased from history, their narratives, recording their experiences on the controversial terrain in South Africa, tried to prevent them from being erased by history. Evolving around the notion of threat that is at the heart of war, the unjustifiable nature of the conflict is ingeniously conveyed in its displacement and complexification.